Retroversion angle of the glenoid cavity in South Indian population - S V Uma; V Balasubramanyam (Wolters Kluwer Medknow Publications, 2016)
Background and aims: Glenoid version angle is tilt of glenoid cavity in relation to the plane of scapula, it is recorded as anteversion if glenoid is open anteriorly, and retroversion if it faces posteriorly. The tilting angle of the glenoid cavity has a role in shoulder stability. In end-stage glenohumeral arthritis, wear is usually greater in the posterior half of the glenoid articular surface effectively increasing glenoid retroversion (RV). Aligning the glenoid prosthesis to the face of retroverted glenoid increases the risk for glenoid implant loosening. As Indian literature for retroversion is limited, this study was undertaken. The aim was to estimate and compare the version angle of the glenoid cavity of right (Rt) and left (Lt) dry scapulae. Material and Methods: Superior view of 200 dry scapulae (100 right and 100 left) were photographed using a digital camera. The images were transferred to Microsoft power pointR 2007 software and using Image J software glenoid version angle were measured. Results were analysed using SPSS 16. Independent sample t test was used to compare right and left sides. Results: Ninety eight of hundred Lt glenoid were retroverted with a mean angle -5.02 ± 2.07°, two were anteverted with mean value+1.65°. All the 100 Rt glenoid were retroverted with mean of -6.90 ± 3.48°. There is significant difference in the angle of glenoid version of left and right glenoid cavity with a p value <0.01. Conclusion: Proper implant positioning is key issue in shoulder arthroplasty for efficient postoperative function and long-term survival of the implant. Hence preoperative assessment of glenoid version is essential.